Methods of teaching in Islam and incorporating certain ideas into the teaching of the modern medical Science in India: Some thoughts and some observations - N Ganguly, Narendra; Phukan Ray, Rituparna (International Journal of Medical Research and Review, 2019)
The fast progress of the Medical Science as well as introduction of newer technologies makes Teaching in Medical science challenging. It is difficult to teach the Medical students in all the aspects of medical science and produce good, well learned, treating doctors within a span of four and a half years. Introduction of non treating branches in the final MBBS, as clinical subjects, has compounded the problem. The paucity of time to teach the treating branches in the final year, has caused confusion amongst the mind of the teachers of the treating branches. In such a scenario, we thought that it is worth to look into the ancient methods of teaching, which are still relevant in today’s world. The present activities of the MCI, is confusing. The effort of re teaching the old and senior teachers, how to teach, is failing. This necessitates re-look into the past to introduce new ideas into medical education methodology. Here we look into the system of teaching followed by the Islamic faith. Islamic scholars spread the light of knowledge to the west. They were voracious observers, readers as well as energetic writers. These scholars took the wisdom of the east to the wild of the west. Although the journal publications on the subject of Islamic methodologies are sparse, the materials available are very useful in providing an insight to the teaching methods in Islam. Following the disciplined methods, the students learn without fail and spread the gist of knowledge in the society around. It is worth to look into the methods of the teaching in this one and half millennia old system and see if some input can be made into the modern methodology of teaching in the modern Medical Education delivery in India. The available literature on the subject sheds enough light to the teaching methods in Islam. Many of these steps can be incorporated in the teaching methodology in the Medical education in India. Especially introduction of the AETCOM and the faculty development program by the MCI recently, are good in intentions but has opened up new challenges and questions. This may lead to the dilution of the criteria of the teachers of the teachers as a result the damage will be deep and permanent. We discussed some important steps as well as guidelines based on the highly successful teaching methods in Islam in this article for looking to incorporate some of these methods into the MCI Medical education system. Teaching methods in Islam have survived the taste of time and Millennia. It is high time that some of the principles be looked into and utilized to improve the Medical education in India.